Regarding the measurement of therapeutic adherence - Sara Malo (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
Adherence to chronic therapies among population living in developed countries has been estimated about 50% [1]. This is a matter of concern, since poor adherence is associated with suboptimal clinical outcomes, increased frequency of adverse effects and high healthcare expenses [2].